"Há quanto tempo você faz violência sexual?" : análise do atendimento a adolescentes menores de 14 anos, na área da saúde - Venancio, Karen Mirela Sales (2016)
This work aims to analyze the functioning of a health service to people in situations of sexual violence , discussing the admission of adolescents younger than 14 years , with the institutional complaint have been victims of rape, being inserted even those who claim to have had sex with consent, sexual initiation has occurred. In addition, it is proposed to discuss the resurgence of the issue of resulting violence of institutional equipping these adolescents facing the possibility of execution of a protocol service of the Ministry of Health, Ministry of Justice and Department of Policies for Women, for inclusion registration and collection of traces in health services, so that they can serve as a criminal trial for rape. The discussion is conducted from the contributions of Foucault and institutional analysis, considering the notions of history, violence, analysis of the implications and the role of the militant, health-violence interface, from the psychologist of performance experience in a state referral center for victims of sexual violence in the context of health. This research studies on counter- memories and analysis of the implications, in dialogue with some artistic contributions (mandalas and poetry) in an attempt to analyze how institutionalized health discourses can produce the notion of a victim of sexual violence for these adolescents. The focus is precisely demarcate that despite being widely reported as an area of confrontation of violence, a reference service sometimes can become a producer of what publicize be his greatest enemy : an aggressor, and more specifically, against adolescents who exhibit have had their sexual initiation before the legally permitted period.